2002
DOI: 10.1055/s-2002-25151
|View full text |Cite
|
Sign up to set email alerts
|

Chances and Shortcomings of Adenovirus-Mediated ATP7B Gene Transfer in Wilson Disease: Proof of Principle Demonstrated in a Pilot Study with LEC rats

Abstract: The data demonstrate proof of principle of successful gene therapy in an experimental model of WD. As a consequence of successful but only transient therapeutic effect of adenoviral gene transfer we can now focus more efficient and permanent gene transfer strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Previous studies demonstrated that introduction of a functional ATP7B gene in LEC rats showed restoration of biliary copper excretion 103. However, these studies did not achieve sustained effects because of the short duration of transgene expression using the first-generation adenoviral vectors.…”
Section: Treatment Of Wdmentioning
confidence: 99%
“…Previous studies demonstrated that introduction of a functional ATP7B gene in LEC rats showed restoration of biliary copper excretion 103. However, these studies did not achieve sustained effects because of the short duration of transgene expression using the first-generation adenoviral vectors.…”
Section: Treatment Of Wdmentioning
confidence: 99%
“…The limitations of this test are restrictions in copper isotope use in laboratories, so currently it is performed rarely for diagnostic needs. Radioactive copper test is regarded as a useful tool in experimental works where the aim is to restore function of mutated gene and potentially could be used in human gene therapy studies [7,8].…”
Section: To the Editorsmentioning
confidence: 99%
“…Noninvasive diagnosis of WD, particularly at an early state, will be significant, because copper can be mobilized by drugs or possibly by cell or gene therapy approaches (1,47). Previously, diagnosis of WD with radiocopper was unsuccessful.…”
mentioning
confidence: 99%